HR-DIGITAL: DIGITAL TECHNOLOGIES IN HUMAN RESOURCES MANAGEMENT (Development Service Industry Management, 2023)
Globalization, changes in consumer behavior, transition to networked digital economy: speed and mobility, digitalization - contemporary trends driving companies to seek new competitive business management models. Formation and development of digital strategy integrated with business and HR strategies becomes a necessary condition for ensuring future competitiveness through business transformation from traditional to technological enterprises. Benchmarking has identified the prerequisites for HR-Digital: changes in consumer behavior have influenced the active development of a cluster of companies leading online businesses. New business models have transformed labor and human resources management, shaping HR trends that introduce new approaches to enhancing efficiency: business-oriented HR, philosophy of agility, freedom: transition to virtual workplaces and flexible employment, digitalization development. The article provides an overview of HR-Digital implemented across companies in various industries, demonstrating the diversity of opportunities offered by automated and digital technologies in all areas of human resources management: mobile employer; development of corporate social networks; mobile applications as primary platforms for HR tools; learning anytime and anywhere; intellectualization and robotization; personalized approach and cognitive technologies. Demand drives supply - active development of companies creating products and offering digital technology services in the HR sector is noted.
Keywords: business management approach; mobility; digitalization; benchmarking; digital strategy; HR management; HR trends; digital technologies in human resources management